Dilema Kewargaan Kelompok Minoritas: Studi Kasus Suku Bajo di Nusa Tenggara Timur: Dilema Kewargaan Kelompok Minoritas: Studi Kasus Suku Bajo di Nusa Tenggara Timur - Abu Bakar Bakar; Nila Sastrawati (LIPI Press, 2021)
This paper discusses the issue of citizenship of the Bajo ethnic minority group on Kera Island, Kupang Regency,East Nusa Tenggara Province. The general question in this study is what are the implications of state politics forcitizenship in the case of the Bajo tribe on Kera Island?. To answer this question, the concept of citizenship is usedas an analytical tool. This research uses qualitative research, with a case study research design. This researchconcludes that the Bajo people as a minority group in East Nusa Tenggara find themselves in a dilemma. Onthe one hand, the state considers the Bajo people on Kera Island as squatters who are not entitled to citizenshipstatus, therefore they do not get their rights, especially with regard to basic services. But on the other hand, theBajo people are still involved in the electoral process to determine people’s representatives. In this condition, theBajo people feel that their citizenship status is only given as long as it relates to the interests of the state and isforgotten again when the state no longer has an interest.